Tingkat Kepuasan Konsumen di Rumah Makan Sonder Indah - Rori, Cevita M.; Ruauw, Eyverson; Rengkung, Leonardus Ricky (Sam Ratulangi University, 2023)
This study aims to determine the level of customer satisfaction with products, prices, places and services of RM Sonder Indah. This research was conducted from September to October 2022. The data used in this study are primary data and secondary data. Primary data was obtained through direct interviews with 30 respondents using a questionnaire measured using a Likert scale. Secondary data obtained through books, journals, and literature related to this research topic. The results showed that the level of consumer satisfaction at RM Sonder Indah from the product, price, place and service variables was 82.04%, generally classified as very satisfied. RM Sonder Indah's customer satisfaction level for the product variable category is 84.45%, which is very satisfied, the price variable is 83.99%, it is very satisfied, and the place variable, 80.33%, is very satisfied. For the satisfied category there is a service variable of 79.99%.